Penerapan Pembelajaran Berdiferensiasi dalam Memenuhi Gaya Belajar Siswa Peserta Didik di Sekolah Dasar - Silfia Novita Rizki; Elisa Pitria Ningsih (PT. Anagata Sembagi Education, 2024)
The differentiation approach in learning styles has become a significant subject of attention in the educational context, especially at the elementary school level. This research aims to explore the implementation and impact of differentiated learning on content, processes and learning products in elementary schools based on student learning styles. Based on a review of literature and related research, it was found that content differentiation allows teachers to present open-ended material tailored to students' needs and level of understanding. Meanwhile, process differentiation helps in adopting diverse teaching strategies that suit each student's learning style. Additionally, product differentiation provides students with opportunities to express understanding through different types of assignments or projects, allowing for creative development of talents and interests. The research results show that the approach to learning styles has a positive impact in creating a learning environment that supports and improves overall learning outcomes. Therefore, differentiated learning in elementary schools is becoming increasingly important in supporting the successful learning of each student.